Relationship between the Characteristics of Mothers of Stunting Toddlers and Anxiety Levels - Utario, Yossy; Misniarti, Misniarti; Anugra Jaya, Meigo; Amaliya, Sholihatul; Heni Kusumawardani, Lita (Journal of Bionursing, 2025)
Background: Stunted toddlers experience growth and developmental disturbances, both in the short and long term. The condition of stunted toddlers can lead to anxiety among parents, particularly mothers. Purpose: This study aims to examine the relationship between the characteristics of mothers with stunted toddlers and their level of anxiety. Methods: This research is a quantitative study with a cross-sectional approach. Sampling was conducted using a purposive sampling technique, with a total of 60 mothers who have stunted toddlers as respondents. Data was collected using a respondent biodata questionnaire and the Hamilton Anxiety Rating Scale (HARS) to measure maternal anxiety. Data analysis included univariate analysis to describe the characteristics of maternal anxiety and bivariate analysis using Fisher's exact test. Results: The findings indicate no significant relationship between maternal anxiety and factors such as current maternal age, age at marriage, maternal education, maternal occupation, maternal income, chronic energy deficiency (KEK) during pregnancy, number of children, or the stunting category of the child. Conclusion: The study concludes that there is no significant relationship between the characteristics of mothers (such as current age, age at marriage, education level, occupation, income, history of chronic energy deficiency during pregnancy, number of children, and the child's stunting category) and the level of maternal anxiety. These findings suggest that maternal anxiety in the context of stunted toddlers may be influenced by factors beyond the demographic and socioeconomic characteristics examined in this study. Further research is recommended to explore other potential factors contributing to maternal anxiety in such cases.